ESTABLISHING THE RIGHT OF REFUSAL: PUBLIC SERVICE REFORMS POLICIES AND THE THESIS OF IMPOSITION ON NIGERIA BY EXTERNAL FORCES (International Journal of Scientific Research and Management (IJSRM), 2013)
paper examined the claim that reform policies in the public service of Nigeria especially during the political dispensation between 1999 and 2007 were impositions of the external forces. It did a succinct comparative analysis of some reform policies of some countries including Nigeria taking cognisance of the International Financial Institutions (IFIs) interface relying on data from secondary sources and that of the interviews with sampled civil servants and trade unions officials. It was found out that some of the reform policies were actually beneficial to the service while the countries buying into the policies as “imposed” by the IFIs have a right of refusal.